Annotated list of the plants of the Tortuguero National Park. - Hurtado-Hernández, Priscilla M.; González-Ramírez, José A. (Revista de Biología Tropical, 2013)
The floodplains of Tortuguero, in northeastern Costa Rica, stand as one of the richest plant-species regions in Central America. In this paper, we present the annotated check-list of vascular plants that are present within the rainforest of Tortuguero National Park (TNP), a 26 604h land that protects most of the biological diversity of these plains. Our list resulted from collections made in 2012, as well as the examination of material mantained at the Herbarium of the National Biodiversity Institute of Costa Rica, INBio (ATTA Database) and in the TROPICOS database. A total of 732 vascular plant species included in 413 genera are known to the Park. Two of these species have limited distributions and are endemic to Costa Rica: Pseuderanthemum pittieri (Acanthaceae) and Paullinia austin-smithii (Sapindaceae). Ninety species have known ethnobotanical uses. The high diversity in plant species reported here for the forest environments of Tortuguero contrasts with the low species diversity previously reported in the palm-swamps that characterize the riverine habitats within the Park.